Why did performance-based financing in Burkina Faso fail to achieve the intended equity effects?: A process tracing study - Lohmann, Julia; Koulidiati, Jean-Louis; Robyn, Paul Jacob; Somé, Paul-André; De Allegri, Manuela (Social science & medicine, 2022)
In recent years, performance-based financing (PBF) has attracted attention as a means of reforming provider payment mechanisms in low- and middle-income countries. Particularly in combination with demand-side interventions, PBF has been assumed to benefit also the most vulnerable and disadvantaged groups. However, impact evaluations have often found this not to be the case. In Burkina Faso, PBF was coupled with specific equity measures to enhance healthcare utilization among the ultra-poor, but failed to produce the expected effects. Our study used the process tracing methodology to unravel the reasons for the lack of impact produced by the equity measures. We relied on published evidence, secondary data analysis, and findings from a qualitative study to support or invalidate the hypothesized causal mechanism, that is the reconstructed theory of change of the equity measures. Our findings show how various contextual, design, and implementation challenges hindered the causal mechanism from unfolding as planned. These included issues with the identification and exemption of the ultra-poor on the demand side, and with financial issues and considerations on the supply side. In broader terms, our findings underline the difficulty in improving access to care for the ultra-poor, given the multifaceted and complex nature of barriers to care the most vulnerable face. From a methodological point of view, our study demonstrates the value and applicability of process tracing in complementing other forms of evaluation for complex interventions in global health.
Gesehen am 23.08.2022